Comparison of antibacterial activity inhibitory of black cumin (Nigella sativa) oil, Cresophene®, and Calcium hydroxide - Anggono, Fajar Dwi; Kuswandari, Sri (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
ABSTRACTIntroduction: Black cumin (Nigella sativa) oil is a natural antibacterial product containing thymoquinone. Thymoquinone is a powerful antibacterial substance towards gram-positive bacteria. The research objective was to compare the inhibitory effects of black cumin oil, Cresophene® and Ca(OH)2 towards the growth of Staphylococcus aureus. Methods: Experimental laboratory by taking Staphylococcus aureus from deciduous teeth pulp necrosis that has been isolated in Brain-Heart Infusion (BHI) medium. Inhibitory of black cumin oil, Cresophene® and Ca(OH)2 were measured by making three different 6 mm diameter wells contained each substances. Data then analyzed by two-way ANOVA using statistical analysis program. Results: Cresophene® had the largest inhibitory zone with the average zone was 32 ± 0.05mm and stable from the 1st day until the 4th day then decreased on the 5th day and remain stable until the 7th day. Ca(OH)2 had average inhibitory zone of 15.9 ± 0:10 mm and remain stable from the 1st day until the 7th day. Black cumin oil had average inhibitory zone of ± 7.9 ± 0.2 mm and remain stable from the 1st day until the 7th day. Conclusion: The inhibitory zone towards Staphylococcus aureus isolated from deciduous teeth pulp necrosis consecutively was Cresophene®, Ca(OH)2 and black cumin oil.Keywords: Staphylococus aureus, Black cumin oil, Cresophene®, Ca(OH)2, Inhibitory zone